Hypermobility in patients with epidermolysis bullosa—A retrospective observational study from a national referral center - Maria L. Bageta; Michelle Wood; Pablo Lopez Balboa; Gabriela Petrof; Anna E. Martinez (JEADV Clinical Practice, 2024)
Abstract Background Epidermolysis bullosa (EB) is an inherited genodermatosis of variable severity characterised by skin and mucosal fragility commonly associated with altered gait patterns and hypermobility. Objectives To define the altered gait pattern and identify possible causes in patients with EB. Methods Retrospective review of the EB database to identify children with EB with at least one physiotherapy assessment between 2009 and 2022. Results Forty‐eight children out of 59 referrals to physiotherapy with an altered gait pattern were identified (81.3%); 23 (48%) had recessive dystrophic EB (RDEB), 17 (36%) EB simplex, five (10%) Junctional EB (JEB) and three (6%) dominant dystrophic EB (DDEB). The patho‐mechanical altered gait patterns were characterised by altered load‐bearing surface in contact with the floor (63%), short shuffling pattern with high cadence and decreased single support (42%) and equinovarus (toe walking) (6%). Hypermobility (as defined by the Beighton score) was present in 67% of patients: 43% in RDEB, 88% in EBS, 100% in JEB and 67% in DDEB. Conclusions In this study, we provide the first accurate data for the causes of altered gait patterns in children with EB. Healthcare professionals should be aware of joint hypermobility and its effect on gait in this patient cohort.